Pengaruh Coating Ekstrak Daun Cincau Hijau (Cyclea Barbata L.) dan Suhu Penyimpanan terhadap Perubahan Fisik Tomat (Solanum lycopersicum L.) Selama Penyimpanan - Aisyah, Deva Ayu; Novita, Dwi Dian; Tamrin, Tamrin (abe.fp.unila.ac.id, 2022)
Tomatoes are coated with natural wax from the time they are planted on the tree, but the natural wax coating fades or even disappears due to post-harvest treatment. The coating application serves to replace the wax layer using tapioca with the addition of green grass jelly leaf extract. This study aims to determine the effect of the combination of green grass jelly leaf extract coating with 3 concentrations and 2 temperatures of storage conditions on 4 physical parameters of tomatoes, namely the level of hardness, weight loss, moisture content, and red color index of tomatoes and to determine the best treatment from the combination of treatments applied during storage. This study used a factorial Completely Randomized Design (CRD) with 2 factors. The first factor is storage temperature which consists of 2 temperature levels, namely room temperature (S1) and cold temperature (S2). The second factor is the concentration of green grass jelly leaf extract which consists of 3 levels of extract concentration, namely 10%, 30%, and 50%. If the results of the analysis of variance at the 5% level have a significant effect, a Duncan further test is carried out to see if there is an interaction between treatments. Based on the analysis, the treatment of variations in the concentration of green grass jelly leaf extract and storage temperature affected 3 physical parameters of tomatoes, namely the level of hardness, water content, and red color of tomatoes. However, it did not affect the weight loss parameters during 13 days of storage. S2K2 treatment was able to maintain the level of hardness, moisture content, and red color of tomatoes on day 13 with the standard of weight loss 10%. Based on further observations, the S2K2 treatment was able to maintain the shelf life of tomatoes up to 27 days of storage. Keywords: Coating, Concentration of Grass Jelly Leaf Extract Green, Storage Temperature, Tomato.